Growing semiconductor nanocrystals directly in a conducting polymer - Watt, A; Rubinsztein-Dunlop, H; Meredith, P (2005)
We describe a single step method to synthesise lead sulphide (PbS) nanocrystals directly in the conjugated polymer poly (2-methoxy-5-(2′- ethyl-hexyloxy)-p-phenylene vinylene) (MEH-PPV). This method allows size control of the nanocrystal via co-solvent ratios. We find good agreement between nanocrystal sizes determined by transmission electron microscopy and sizes theoretically determined from the absorption edge of the nanocrystals. Finally we show that this synthesis technique is not restricted to MEH-PPV and demonstrate that nanocrystals can be grown in Poly(3-hexylthiophene-2,5-diyl) (P3HT). © 2005 Elsevier B.V. All rights reserved.